The Effect of Applying JOIN Strategy on Developing Iraqi EFL College Students’ Comprehension of Short Stories - Yahya, Nagham Qadoori; Saloomi, Ismail Dawood (Journal of Tikrit University for Humanities, 2020)
There has been an increasing recent interest in using JOIN strategy in teaching various aspects of EFL. This study tries to find out the extent to which this strategy can be applied to teaching short stories. It also aims to find out whether or not using this strategy can lead to any progress in developing students’ comprehension of short stories. To conduct the study, it is hypothesized that there is no statistically significant differences between the mean scores of the experimental group, which is taught by the JOIN strategy and the control group which is taught by the traditional strategy in the posttest achievement in short stories. To achieve the aim of the study and verify its hypotheses two types of procedures have been following: Theoretical and practical. The theoretical procedures consist of presenting a theoretical framework of JOIN strategy including their characteristics, principles, The practical procedures consist of conducting an experimental which last for fifteen weeks. The total numbers of sample subjects was (75) students: (35) in experimental group and (40) students in the control group. The two groups were exposed to an achievement posttest after ensuring its validity and reliability. Suitable statistical tools have been used to analyses to the results of the study. The results have also shown that there was a significant difference between the mean scores of the experimental group and the control group in favour of the experimental group.